STRUCTURING POTENTIAL OF COVER CROPS IN A CLAYEY OXISOL AND THEIR EFFECT ON CRAMBE GRAIN YIELD AND OIL CONTENT - Rosa, Helton Aparecido; Secco, Deonir; Santos, Reginaldo Ferreira; Ciotti de Marins, Araceli; Fornasari, Carlos Henrique; Veloso, Gustavo (Scientia Agraria, 2018)
This study aimed to assess the potential of twelve cover crops in improving the structural state of the soil evaluating soil bulk density and soil resistance to penetration and their effects on crambe grain yield and oil content. The experiment was conducted at the Experimental Center of Agricultural Engineering (NEEA), at the State University of West Paraná (UNIOESTE) - Cascavel - Paraná. The cover crops were named as treatments and consisted of twelve species, namely: Crotalaria juncea, Crotalaria spectabilis, Pigeon pea, Jack bean, Foxtail millet, Forage sorghum, Lablab beans, Guandu beans, Mucuna aterrimum, Mucuna Pruriens, Mucuna deeringiana, Mucuna aterrima, and a control treatment (fallow area). The experimental design used consisted of randomized blocks with four replications and plots measuring 5 x 5 m. When species were in full bloom in May 2010, they were managed by desiccation with non-selective herbicide and subsequent mowing in order to accelerate the decomposition rate of their roots. In August 2011 we performed the planting of crambe for further analysis of its grain and oil yield. In January 2012 soil samples were collected to evaluate soil bulk density by the volumetric ring method at depths of 0.0-0.1, 0.1-0.2 and 0.2-0.3 m. Soil resistance to penetration was determined using a penetrometer until 0.4 m deep. In order to determine crambe grain yield, crambe was collected in an area of 4 m2 in the central part of each plot. In ordet tor determe seed oil content it was used the Soxhlet method. The statistical analyzes for soil variables (soil penetration density and resistance) and plant (grain yield and oil yield) consisted of analysis of variance (ANOVA), with a comparison test of mean values. It was also performed linear regression analyzes between data concerning to grain yield and oil yield, as well as grain yield and bulk density. The species Crotalaria spectabilis and Mucuna aterrima provided a significant reduction in soil bulk density when compared to the fallow area, showing higher structuring potential than other species after the first year of use. Considering the structural state of the soil prior to the experiment, with bulk density values lower than 1.2 Mg m-3, there was no significant effect on soil structure by any of the coverage species used and there was also no beneficial effect on crambe grain yield and oil content.